Occupational doses to the eye lens in pediatric and adult noncardiac interventional radiology procedures. Issue 4 (4th March 2021) - Morcillo, Ana Belén; Alejo, Luis; Huerga, Carlos; Bayón, José; Marín, Alberto; Corredoira, Eva; Novo, Joan Ricardo; Hernández, Teresa; Ponce, María Dolores; Garzón, Gonzalo; Vañó, Eliseo; Guibelalde, Eduardo
Abstract : Purpose: To assess occupational lens exposure in a mixed interventional radiology department, comparing pediatric and adult procedures. To analyze the correlation between the lens dose and the doses measured at the chest and collar level and the kerma‐area product (PKA ). Methods: For 17 months, three radiologists performing both pediatric and adult interventions were monitored by means of 14 dosimeters per worker: 12 single‐point optically stimulated luminescent (OSL) dosimeters calibrated in terms of Hp (0.07) were placed on the inside and outside of two pairs of lead glasses, one for pediatric procedures and one for adult interventions; another whole‐body OSL dosimeter calibrated in terms of Hp (10) was placed over the thyroid shield; finally, an additional active solid‐state dosimeter, also calibrated for Hp (10), was worn on the chest, over the apron. Furthermore, a database was created to register the demographic and dosimetric data of the procedures, as well as the name of the radiologist acting as first operator. Results: For the three radiologists, who performed 276–338 procedures/year (20% pediatric), cumulative annual doses to the left bare eye exceeded 20 mSv (21–61 mSv). Considering the glasses' protection, annual doses exceeded 6 mSv (13–48 mSv) for both eyes. No important differences were observed in lens dose per procedure between pediatric and adult interventions (0.16 vs 0.18, 0.12 vs 0.09, and 0.07 vs 0.07 mSv), although lens dose per PKA was 4.1–4.5 times higher in pediatrics (5.8 vs 1.3, 3.3 vs 0.8, and 2.6 vs 0.6 µSv/Gy·cm 2 ) despite a similar use of the ceiling‐suspended screen. Lens doses were highly correlated with collar readings (with Pearson coefficients [r] ranging from 0.86 to 0.98) and with chest readings (with r ranging from 0.75 to 0.93). However, slopes of the linear regressions varied greatly among radiologists. Conclusions: There is real risk of exceeding the occupational dose limit to the eye lens in mixed interventional radiology rooms if radiation protection tools are not used properly. Regular monitoring of the lens dose is recommended, given lens exposure might easily exceed 6 mSv/yr. Using a collar dosimeter for this purpose might be suitable if it is preceded by an individualized regression analysis. The same radiation protection measures should be applied to interventional radiologists regardless of whether they are treating pediatric or adult patients.